Pengaruh Kompetensi, Pengembangan Karir dan Kepuasan kerja terhadap Kinerja Pegawai - Aminah, Aminah; Khotimah, Khusnul; Irawan, Andri; Mustajab, Duta (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study is associative research aiming to analyze, identify, and explain the influence of Competence, Career Development, and Job Satisfaction on Employee Performance at the Ministry of Religious Affairs of Jayapura City, Papua Province. The data used in this research consist of 72 respondents from a total population of 254 employees, sampled using the Slovin Method with Simple Random Sampling as the Probability Sampling technique. The data source is primary data obtained from distributing questionnaires to all respondents. The statistical method employed to test the hypotheses is multiple linear regression analysis with the assistance of SPSS. The analysis results indicate that Competence, Career Development, and Job Satisfaction variables, both partially and simultaneously, positively and significantly affect the performance of Ministry of Religious Affairs employees in Jayapura City. This study not only highlights the dynamics within the Ministry of Religious Affairs in Jayapura City, Papua Province but also contributes to a deeper understanding of the factors influencing employee performance.